Методология разработки технологий извлечения знаний из клинических данных индуктивными методами - Савченко, Е.А.; Поднебесная, Г.А.; Долгополов, И.Н. (Міжнародний науково-навчальний центр інформаційних технологій і систем НАН та МОН України, 2009)
Development of technology of data analysis and knowledge extraction from an experimental data sample by inductive methods is described on the example of decision of tasks of clinical diagnostics. This technology includes the tasks of the preliminary data processing, classification, clusterization, management and prognosis models construction. The generalized model construction of the patient state with ischemic heart trouble for the patients state management is offered.